The effect of carbonized rice hull on the growth of Swietenia macrophyllaseedlings in a containerized seedling production system. - Memoracion, Kevin Ray C. (Kevin Ray C. Memoracion, 2018)
Carbonized rice hull (CRH) or rice hull biochar has been used for soil improvement in agriculture but there are very few studies of its uses in forestry. The purpose of this study was to investigate the effect of CRH on the growth of Swietenia macrophylla seedlings and to determine the best ratio of CRH application as a parameter for this tree's production. S. macrophylla was used to determine the effects in a containerized seedling production system because of the species' high economic value as commercial timber and as a street tree species. Eight different percentages of CRH application was used and each of these treatments had 10 replicates. The dry weight and root collar diameter improved significantly using 20-25% CRH applications compared to other percentages while the height best improved using 15-25% applications. Dickson's Seedling Quality Index also showed that best growth was attained at 20-25% applications. The study shows that biochar made from rice hull can be substituted for growing medium by 20-25% in a containerized seedling production system.